Blunders of Government Communication: The Political Economy of COVID-19 Communication Policy in Indonesia - Masduki Masduki (Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
Government officials and politicians have been both a help and hindrance in the public dissemination of information during the COVID-19 pandemic. The intervention of a president and his/her ministries with their political and economic interests is particularly problematic when they employ a tactical approach rather than provide accurate and effective disaster information. This paper utilizes a political-economy approach to analyze the link between COVID-19 communication policies and practices with the interests of politics and market stability in Indonesia. In this paper, the author drills into the extent to which the country’s president and ministries manage their political interests in times of global pandemic. The ways they interact with the public during various stages of disaster are crucial because society is severely disrupted, with the government serving as the sole actor. This study uses qualitative methods and all materials are managed from an extensive review of current literature, policy analysis, and field observation. This paper finds that Indonesian government communication during the COVID-19 pandemic period (February– June 2020) has been dominated by a desire to maintain a strong power of the ruling authority and to secure market stability. Two factors—pro-market communication policies and manufactured- politicized COVID-19 data—have occurred. This paper contributes to the literature by focusing on the political and economic approach over the mediated discourses surrounding the pandemic.